Active aging in the workplace: Challenges and strategies in EU countries - Ivan DE SANTIS; Angelo SACCO (GIornale Italiano di Psicologia e Medicina del Lavoro, 2023)
Active aging, defined by WHO, aims to optimize health and participation for older individuals, improving their quality of life. The aging workforce challenges organizations but offers benefits such as increased productivity and diverse experience. Europe’s aging population calls for strategies to accommodate older workers. Active aging fosters physical and mental well-being, social inclusion, and reduced disease risk. Employers must implement a comprehensive approach, addressing psychosocial risks, providing continuous training, and considering reasonable accommodations. Promoting active aging benefits individuals, organizations, and society. In this commentary, we present the challenges and issues that the topic poses in Italy and in European countries.